2019
DOI: 10.1038/s41393-019-0379-9
|View full text |Cite
|
Sign up to set email alerts
|

The associations of acceptance with quality of life and mental health following spinal cord injury: a systematic review

Abstract: Study Design: Systematic review. Objectives: To identify, critically appraise, and synthesize research findings on the associations between acceptance, quality of life (QOL), and mental health outcomes in individuals living with spinal cord injury (SCI). Methods: Five databases (PubMed, PsycINFO, Embase, Web of Science, and Scopus) were systematically searched. Studies were included if they provided findings on the association between acceptance and QOL, mental health outcomes, or both in an SCI population age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 66 publications
(167 reference statements)
5
26
0
Order By: Relevance
“…With respect to the positive and negative affects before and during lockdown, the results of the present study show that participants' PA scores fell and their NA scores increased while under quarantine, wherein the differences were significant and of moderate to high magnitude. Several studies have found that the greatest impact of an epidemic on mental health is the increase in anxiety, panic, anger, disappointment, sleep problems, disturbances in circadian rhythms, as well as depressive and post-traumatic stress symptoms (Halperin, 2014;Hackett and Steptoe, 2017;Aaby et al, 2020;Zhang and Ma, 2020). Specifically, confinement increases an individual's levels of confusion, irritation, fear, pain, numbness, and anxiety-induced insomnia (Brooks et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the positive and negative affects before and during lockdown, the results of the present study show that participants' PA scores fell and their NA scores increased while under quarantine, wherein the differences were significant and of moderate to high magnitude. Several studies have found that the greatest impact of an epidemic on mental health is the increase in anxiety, panic, anger, disappointment, sleep problems, disturbances in circadian rhythms, as well as depressive and post-traumatic stress symptoms (Halperin, 2014;Hackett and Steptoe, 2017;Aaby et al, 2020;Zhang and Ma, 2020). Specifically, confinement increases an individual's levels of confusion, irritation, fear, pain, numbness, and anxiety-induced insomnia (Brooks et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Using the SCI QL-23, Elfström et al [4] found that the use of appropriate coping strategies with higher acceptance and lower social reliance contribute to a greater HRQoL. Similar results were found in a recent systematic review where acceptance coping was associated with higher levels of QoL [5]. However, conflicting results have been found how different domains of HRQoL are associated with age, gender and injury characteristics [6][7][8][9].…”
Section: Introductionmentioning
confidence: 76%
“…Within SCI research, awareness of acceptance is increasing. Aaby et al [27] emphasized that acceptance is a psychological resource that healthcare professionals can work to support to improve quality of life and mental health following SCI. Incorporating Stroebe and Schut's dual process model of coping with bereavement can aid in understanding how loss and acceptance relate to transfer of knowledge and skills [28].…”
Section: Discussionmentioning
confidence: 99%